Islamic Family Law and Household Financial Sustainability: Contemporary Challenges in the Asia-Pacific Region - Wahyu Abdul Jafar (PT. Islamic Research Publisher, 2025)
The sustainability of household finances has emerged as a critical issue within contemporary Muslim societies, particularly in the Asia-Pacific region, where rapid economic transformation, digital financialization, changing family structures, and increasing living costs have significantly influenced family welfare. This study aims to examine the relationship between Islamic family law and household financial sustainability by analyzing contemporary challenges faced by Muslim families in the Asia-Pacific context. The research specifically explores how Islamic legal principles governing family rights and obligations, wealth management, maintenance (nafaqah), inheritance, and marital economic responsibilities contribute to the creation of sustainable household financial systems. This study employs a qualitative normative approach based on an extensive literature review of scholarly articles, legal documents, policy reports, and contemporary studies related to Islamic family law and family economics. Data were collected from reputable academic databases and analyzed using a thematic-content analysis framework to identify major patterns, emerging challenges, and legal responses across selected Asia-Pacific countries. The findings reveal that household financial sustainability is increasingly challenged by economic uncertainty, dual-income family dynamics, digital consumerism, rising household debt, gender role transformations, and disparities in financial literacy. The study demonstrates that Islamic family law provides a comprehensive framework for promoting financial resilience through principles of justice, shared responsibility, wealth preservation (hifz al-mal), balanced consumption, and intergenerational economic protection. However, the implementation of these principles often faces institutional, socio-cultural, and regulatory constraints within contemporary societies. The analysis further indicates that integrating Islamic legal values with modern financial governance and family welfare policies can strengthen household economic stability and social well-being. This study contributes to the growing discourse on Islamic family law by connecting classical legal doctrines with contemporary household financial sustainability challenges. It offers a multidisciplinary perspective that enriches discussions on family welfare, Islamic economics, and socio-legal reform, particularly within the diverse and rapidly evolving Asia-Pacific region.